2012
DOI: 10.1159/000338347
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Patients with Antiphospholipid Syndrome Who Undergo Percutaneous Coronary Intervention

Abstract: Objectives: Patients with antiphospholipid antibody syndrome (APS) have an increased risk of atherothrombotic complications. There are limited data regarding the outcome of patients with APS who undergo percutaneous coronary intervention (PCI). Accordingly, we aimed to assess the long-term outcomes of these patients. Methods: Nineteen APS patients who underwent PCI between the years 2003 and 2008 were compared to 380 patients who had undergone PCI during the same period (PCI group) and were matched by age (±5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 68 publications
(37 reference statements)
0
26
0
4
Order By: Relevance
“…The study by Perl et al in 2011 also showed a remarkably higher rate of repeated revascularization (target vessel revascularization) in patients with APS who underwent coronary angioplasty despite a similar use of drug eluting stents and diabetic status in both the experimental and the control group. 11 The study by Smythe et al in 1976 showed an increased incidence of MI among patients with SLE, which resulted in an increased mortality rate among such patients. The study by Hak et al 21 also concluded that they found a statistically increased risk of cardiovascular diseases among patients with SLE.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Perl et al in 2011 also showed a remarkably higher rate of repeated revascularization (target vessel revascularization) in patients with APS who underwent coronary angioplasty despite a similar use of drug eluting stents and diabetic status in both the experimental and the control group. 11 The study by Smythe et al in 1976 showed an increased incidence of MI among patients with SLE, which resulted in an increased mortality rate among such patients. The study by Hak et al 21 also concluded that they found a statistically increased risk of cardiovascular diseases among patients with SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Available data on the short and long-term outcome of PCI in APS patients come from reports, some of which come date before the new era of stents and contemporary PCI techniques [63][64][65][66]. More recently, a retrospective study assessed the long-term outcome of patients with APS who underwent PCI [67]. The investigators report worse long-term clinical outcomes mostly driven by higher rates of thrombotic recurrences without an increase in mortality with respect to controls [67].…”
Section: Embolization To Coronary Arteriesmentioning
confidence: 99%
“…More recently, a retrospective study assessed the long-term outcome of patients with APS who underwent PCI [67]. The investigators report worse long-term clinical outcomes mostly driven by higher rates of thrombotic recurrences without an increase in mortality with respect to controls [67].…”
Section: Embolization To Coronary Arteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] przeprowadzone w grupie 1000 pacjentów z APS, w której drugą z kolei przyczyną zgonu po infekcjach bakteryjnych (21%) był zawał serca (19%). Stwierdzono, że pacjenci z aPL poddani przezskórnej interwencji wieńcowej częściej wymagają rewaskularyzacji i występuje u nich więcej ponownych epizodów sercowo-naczyniowych w obserwacji odległej niż u osób bez tych przeciwciał [10]. Zawał serca jest kontrowersyjnym wskazaniem do diagnostyki trombofilii, którą jednak należy rozważyć u chorych poniżej 50.…”
Section: Opis Przypadkuunclassified